1998
DOI: 10.1103/physrevlett.80.2346
|View full text |Cite
|
Sign up to set email alerts
|

Chain Motion in an Unentangled Polyethylene Melt: A Critical Test of the Rouse Model by Molecular Dynamics Simulations and Neutron Spin Echo Spectroscopy

Abstract: We have investigated the dynamic structure factor for single-chain relaxation in a polyethylene melt by means of molecular dynamics simulations and neutron spin echo spectroscopy. After accounting for a 20% difference in the chain self-diffusion coefficient between simulation and experiment we find a perfect quantitative agreement of the intermediate dynamic structure factor over the whole range of momentum transfer studied. Based on this quantitative agreement one can test the experimental results for deviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
174
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(207 citation statements)
references
References 17 publications
32
174
1
Order By: Relevance
“…The dynamic structure factor of a single chain can be calculated by noting that the random displacements of the normal coordinates are Gaussianly distributed. 2 After some straightforward calculation we find S͑q,t ͒ϭ 1…”
Section: Dϭ K B T N ͑A7͒mentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamic structure factor of a single chain can be calculated by noting that the random displacements of the normal coordinates are Gaussianly distributed. 2 After some straightforward calculation we find S͑q,t ͒ϭ 1…”
Section: Dϭ K B T N ͑A7͒mentioning
confidence: 99%
“…Several other studies have been reported on simulations of melts of polymers of comparable size. [1][2][3][4][5][6][7][8][9] They all suggest that individual properties of these melts can well be described by the Rouse model. 10 In this paper we will test whether the Rouse model can be used to predict the time correlation functions of a comprehensive set of physical processes by using one single set of parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such simulations have been performed only for medium length chains where large-scale dynamics and rheological properties seem to be well described in terms of the simple Rouse model. [5][6][7][8][9] In order to simulate dynamical and rheological behavior of long chains, one has to resort to coarse-grained models. Many different coarse-grained models have been reported in the literature, 10 being perhaps the most popular one that of bead-spring type, where the polymer chain is represented as a sequence of beads connected by springs.…”
Section: Introductionmentioning
confidence: 99%
“…These values are in good agreement with those reported in the literature, as obtained from experimental evaluation. 46 The self-diffusion coefficient increases with increase in temperature and also with increase in the concentration of CNTs.…”
Section: Resultsmentioning
confidence: 99%